MODEL FASIES KARBONAT FORMASI BATURAJA, LAPANGAN DANENDRA, CEKUNGAN SUMATRA SELATAN - Triana Susilowati; Suyoto Suyoto (Jurnal Ilmiah MTG, 2009)
The Early Miocene Carbonate Rock is an important rock reservoir in Indonesia. South Sumatra Basin has several reservoir carbonate which still productive. Danendra Field is one of carbonate rock case studies which can be identified from well and seismic data and then occasionally build-ups and mounds of reefal. Facies carbonate subsurface analysis were done by using seismic data of 7 profiles, 10 well data and one biostratigraphy of one well. The research methodology applied in this research is interpretation of sedimentation, manual correlation, and subsurface mapping. Biostratigraphicaly Baturaja Formation was sedimentated during Early Miocene. Four facies have been identified at Danendra Field, namely a facies shelf characterized by packstone texture, a facies shelf edge / core reef by the present of boundstone texture, a facies lagoon with mudstone-wackstone texture and finally a tidal flat facies demonstrates the grainstone-packstone texture. Stratigraphicaly, Baturaja carbonate can be subdivided into five cycles, the cycles bounded by conformity, except the fourth cycle bounded by disconformity due to the erosion. The process of the first cycle is a sedimentation toward marine and then progradational and retrogradational processes at the second cycle is can be recognized by progradational sedimentation processes, the third cycle a retrogradational process can be identified, and eventually the fourth cycle illustrated by agradational and retrogradational. Sedimentation processes to land ward and finally the fifth cycle characterized by progradational process. Sedimentation environment of Baturaja carbonate was sedimented marine back arc basin due to sea level changing relatively. Age of Baturaja carbonate is Early to Middle Miocene. The Caliche can be found as a result of weathering of Baturaja carbonate diagenetic process. The moldic and vuggy are formed by dissolve process, all diagenetic processes occurred in vadose environment.The most appropriate Baturaja carbonate facies model is an isolated platform with the model of rimmed shelf accretionary.